Toward a Standard Measure of Abortion Service Quality-A Stakeholder First Approach - Chakraborty, Nirali M.; Pearson, Erin; Gerdts, Caitlin; Baum, Sarah E.; Powell, Bill; Montagu, Dominic (Frontiers in Global Women's Health, 2022)
Measurement of the quality of abortion services is essential to service improvement. Currently, its measurement is not standardized, and some of the tools which exist are very long, and may deter use. To address this issue, this study describes a process used to create a new, more concise measure of abortion care quality, which was done with the end users in mind. Using a collaborative approach and engaging numerous stakeholders, we developed an approach to defining and selecting a set of indicators, to be tested against abortion outcomes of interest. Indicators were solicited from 12 abortion service provision entities, cataloged, and grouped within a theoretical framework. A resource group of over 40 participants was engaged through surveys, webinars, and one in-person meeting to provide input in prioritizing the indicators. We began with a list of over 1,000 measures, and engaged stakeholders to reduce the list to 72 indicators for testing. These indicators were supplemented with an additional 39 indicators drawn from qualitative research with clients, in order to ensure the client perspective is well represented. The selected indicators can be applied in pharmacies, facilities, or with hotlines, and for clients of surgical or medical abortion services in all countries. To ensure that the final suggested measures are most impactful for service providers, indicators will be tested against outcomes from 2,000 abortion clients in three countries. Those indicators which are well correlated with outcomes will be prioritized.